Anesthesia Services for Children's Radiotherapy During Pandemic COVID-19 in 2020: Experience from East Indonesia - Anna Surgean Veterini; Herdiani Sulistyo Putri; Ulinta Purwati Pasaribu (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2022)
Background: The global COVID-19 pandemic has significantly strained the healthcare sector, with overwhelmed health services in affected countries worldwide. Despite the need to sustain vital oncology treatments, particularly for children, radiotherapy practitioners are unsure how to treat during the pandemic. At the same time, several anesthesia procedures may increasingly expose anesthesia providers to COVID-19. The challenging services for handling oncology cases in children at Dr. Soetomo Hospital during the COVID-19 pandemic can be carried out properly with various adjustments. Objective: The purpose of this study was to describe how the radiotherapy center in East Indonesia responds to the challenge in this pandemic era.Method: During 2020, we gathered information by using administrative datasets on the number of patients, the types of anesthesia services provided, and undesired events in the radiotherapy room. We use descriptive statistics to describe what is going on in our data.Result: The total number of patients who underwent radiotherapy was 12, with 188 sessions, and uncooperative children received midazolam and propofol during the procedure. The result showed that there was no untoward incident in 2020.Conclusion: Therefore, it indicates that we provided relatively safe sedation services for children's radiotherapy.